Translation strategies, contradiction, and the theory of social representations: Why discussing needles may improve blood donor retention. (15th February 2017) - Moloney, Gail; Hayman, Jane; Gamble, Marguerite; Smith, Geoff; Hall, Rob
Abstract : Retaining blood donors is a cost‐effective way of ensuring a safe blood supply, yet despite the plethora of research, only 5.1% of the eligible population in Australia donate blood and 40% of these do not make a second donation. We offer an alternative to traditional approaches by conceptualizing blood donation within social representations theory as socially derived symbolic knowledge with a specific focus on cognitive polyphasia and Guimelli's (1998) normative and functional dimensions. An online survey, completed by 703 residents from NSW Australia, comprised a blood donation word association task, Likert‐style questions constructed from previous word association data and contextualized blood donation statements. Individual difference scaling analysis revealed all donor groups (including non‐donors) associated blood donation with a few central, albeit contradictory ideas/beliefs. Exploratory factor analysis and confirmatory factor analysis performed on a split data set of the Likert‐style items reiterated this finding. Interpreted through Guimelli's dichotomy, all donor groups were aware of these contradictory normative and functional ideas/beliefs but when explicitly asked, it was the functional aspect that differentiated the groups. We argue the key to retaining donors is understanding the interdependence between how blood donation is socially understood at the societal level of discourse and donor behaviour. Translational strategies for recruitment and retention are discussed.